Market-based Eurobonds Without Cross-Subsidisation - Manasa Gopal; Markus Pasche (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
Most current Eurobond proposals imply substantial cross-subsidisation since some countries partially pay the risk premia for others, thus creating moral hazard and disincentives for fiscal discipline. We suggest, instead, to use standard technologies of financial intermediation like pooling and collateralizing risks. The proposed Eurobond system decreases the costs for all participating nations which is Pareto improving. Since collateral requirements are calculated on individual risk, we eliminate cross-subsidisation. It is essential for the model that a significant fraction of governmental bonds is still issued individually since the model utilizes the risk perception abilities and disciplinating functions of the private capital market. We also discuss institutional issues of possible implementations.
urn:nbn:de:gbv:27-20131126-102314-8
Keywords: E62; E63; H63; 330; sovereign debt; Eurobond; collateral; pooling; cross-subsidisation; Öffentliche Anleihe; Eurobond; Kreditsicherung; Quersubventionierung; Risikoprämie; Theorie; Eurozone